Intratracheal instillation of single-wall carbon nanotubes in the rat lung induces time-dependent changes in gene expression - Fujita, Katsuhide (Nanotoxicology, 2015)
The use of carbon nanotubes in the industry has grown; however, little is known about their toxicological mechanism of action. Single-wall carbon nanotube (SWCNT) suspensions were administered by single intratracheal instillation in rats. Persistence of alveolar macrophage-containing granuloma was observed around the sites of SWCNT aggregation at 90 days post-instillation in 0.2-mg- or 0.4-mg-injected doses per rat. Meanwhile, gene expression profiling revealed that a large number of genes involved in the inflammatory response were markedly upregulated until 90 days or 180 days post-instillation. Subsequently, gene expression patterns were dramatically altered at 365 days post-instillation, and the number of upregulated genes involved in the inflammatory response was reduced. These results suggested that alveolar macrophage-containing granuloma reflected a characteristic of the histopathological transition period from the acute-phase to the subchronic-phase of inflammation, as well as pulmonary acute phase response persistence up to 90 or 180 days after intratracheal instillation in this experimental setting. The expression levels of the genes Ctsk, Gcgr, Gpnmb, Lilrb4, Marco, Mreg, Mt3, Padi1, Slc26a4, Spp1, Tnfsf4 and Trem2 were persistently upregulated in a dose-dependent manner until 365 days post-instillation. In addition, the expression levels of Atp6v0d2, Lpo, Mmp7, Mmp12 and Rnase9 were significantly upregulated until 754 days post-instillation. We propose that these persistently upregulated genes in the chronic-phase response following the acute-phase response act as potential biomarkers in lung tissue after SWCNT instillation. This study provides further insight into the time-dependent changes in genomic expression associated with the pulmonary toxicity of SWCNTs.